Factors influencing evidence‐based nursing utilization intention in Korean practice nurses. Issue 6 (1st April 2014) - Park, Jee‐Won; Ahn, Jeong‐Ah; Park, Mi‐Mi
Abstract : The purpose of this study was to describe Korean nurses' perceptions, attitudes and utilization intention for evidence‐based nursing (EBN), and to explore what factors influence utilization intention. We conducted a cross‐sectional survey in 2012. Registered nurses directly involved in clinical practice were recruited at a medical centre in Korea. A total of 420 nurses completed a self‐report questionnaire. Results showed that participants reported moderate scores regarding their perceptions and attitudes towards EBN, and rated themselves as higher than the median for utilization intention. Furthermore, this study revealed that perceptions of and attitudes towards EBN, occupational view and previous EBN education were significant factors affecting utilization intention. Nurse educators and managers should encourage nurses to have better attitudes towards EBN, help them be more satisfied with their work and provide them with appropriate education for EBN to establish evidence‐based practice as a part of daily nursing care.